Adhesive bond-line degradation detection via a cross-correlation electromechanical impedance–based approach. (November 2016) - Dugnani, Roberto; Zhuang, Yitao; Kopsaftopoulos, Fotis; Chang, Fu-Kuo
This article describes how piezoelectric transducers embedded in the adhesive bond-line of lap-joints can be used to effectively monitor structural integrity. Various lap-joint coupons with embedded piezoelectric transducers were manufactured with and without artificial contamination at the bond-line and tested statically and cyclically. A novel scheme based on the electromechanical impedance response of the transducer was implemented to predict the failure of the tested lap-joint samples. The results from the mechanical testing indicated that monitoring the transducer's electromechanical impedance is an effective way of predicting the failure of the bond-line. Specifically for static tests, local damage to the bond-line was consistently detected at approximately 84% of the failure load for transducers located at the center of the bond-line, whereas for transducers embedded near the edge of the bond-line, the failure of the adhesive was detected at 60% of the failure load. Moreover, preliminary fatigue tests showed that significant changes in the electromechanical impedance signals were apparent starting at 60% of the life of the bond-line. In addition to the mechanical testing, the effectiveness of the proposed electromechanical impedance–based scheme was investigated by means of a three-dimensional finite element model corresponding to the specific coupon geometry tested and through a two-dimensional analytical solution.